Development of repetitive current controller using raspberry PI for 3 phase active power filter for nonlinear load improvement - Sulaiman, Nur Na'imah (2015)
This project is about to design the repetitive controller to compensate the distorted current in the three phase power supply by using active power filter (APF). The APF used is three phase bridge inverter which converts DC to AC waveform. The inverter use Metal Oxide Semiconductor Field Effect Transistor (MOSFET). The Raspberry Pi board is used to supply the pulse width modulation (PWM) signal to the APF. Lastly, the repetitive controller is designed so that the PWM generated is the same signal to be compensated by the APF and enhanced distorted current in power supply into the pure AC waveform. In this project, all the ideas have been applied and tried physically and the output of this project is to get pure sinusoidal waveform at the three phase power supply.